Mapping the therapeutic landscape of CRISPR-Cas9 for combating age-related diseases - He, Qiyu; Wang, Yida; Tan, Zhimin; Zhang, Xian; Yu, Chao; Jiang, Xiaoqin (Frontiers in Genome Editing, 2025)
CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats-associated protein 9) has emerged as a transformative genome-editing tool with significant therapeutic potential for age-related diseases, including Alzheimer’s disease, Parkinson’s disease, cardiovascular disorders, and osteoporosis. This study presents a bibliometric analysis of CRISPR-Cas9 research in age-related diseases, identifying key contributors, major research hotspots, and critical technological advancements. While promising applications have been demonstrated in gene repair, functional regulation, and molecular interventions, significant barriers persist, including off-target effects, low delivery efficiency, and limited editing in non-dividing cells. Ethical concerns over germline editing and gaps in long-term safety data further complicate clinical translation. Future directions emphasize the development of high-precision Cas9 variants, homology-directed repair-independent tools, and efficient delivery systems, alongside the establishment of international regulatory frameworks and multicenter clinical trials. These efforts are essential to fully realize the potential of CRISPR-Cas9 in addressing the global health challenges of aging.